Immunoglobulin G4-Related Lung Disease Presenting as Lung Cavitating Mass and Mimicking Lung Cancer - Liang-jun XIE; Jian-fang LI; Zhi LIU; Feng ZHANG; Chang ZHAO; Lu-ping QIN; Ting-jie ZHANG; Mu-hua CHENG (Archives of Rheumatology, 2017)
Immunoglobulin G4-related lung disease (IgG4-RLD) is a disease in which abundant activated IgG4-positive plasma cells and lymphocytes infiltrate lung tissues with high 18F-fluorodeoxyglucose uptake. Although various forms of radiologic features of IgG4-RLD have been reported, cavitating mass is a rare imaging feature and should be differentiated from cancer. Therefore, in this article, we report two cases both with unprovoked cough, bloody sputum and presenting quite similar cavitating lesions with high 18F-fluorodeoxyglucose uptake on positron emission tomography/ computed tomography, one of which diagnosed as IgG4-RLD and the other as lung cancer based on biopsy eventually. The awareness of the imaging features of IgG4-RLD and lung cancer described in the present study may help physicians to distinguish one from the other. IgG4-RLD should be considered in the differential diagnosis of cavitary lung lesions.